Corporate Diversification and the Cost of Debt: The Role of Segment Disclosures - Franco, Francesca; Urcan, Oktay; Vasvari, Florin P. (The Accounting Review, 2016)
ABSTRACT Previous theoretical arguments suggest that industrial diversification provides a co-insurance effect that decreases the firm's default risk. In this paper, we endogenously estimate a firm's segment disclosure quality and investigate whether the quality of segment disclosures significantly affects bond investors' assessment of the co-insurance effect of diversification. We document that bonds issued by industrially diversified firms with high-quality segment disclosures have significantly lower yields than bonds issued by diversified firms with low-quality segment disclosures. We also find that the negative relation between industrial diversification and bond yields becomes stronger when firms improve segment disclosures as a result of FAS 131. Finally, we show that high-quality segment disclosures are associated with lower syndicated loan spreads for a subsample of loans issued by large bank syndicates, which are more likely to rely on publicly reported segment information. JEL Classifications: G31; G32; M10; O16.